Pemrograman Python untuk Analisa Kepuasan Penggunaan Aplikasi Kumon - Susilo , Joko; Yunianto , Imam; Arfani , Berliana Agustin Kusumaning Ayu (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
Kumon is a tutoring place for children in learning math and English. With a method developed by the founder of Kumon with the aim of making it easier for children to understand subjects. My Kumon is an application that can make it easier for students to carry out English teaching and learning activities. The purpose of this research is to measure the satisfaction of using the My Kumon application used at Kumon Radin Inten. Using the Technology Acceptance Model (TAM) and End User Computing Satisfaction (EUCS) methods. The steps taken include observation, data collection, distribution of questionnaires, data calculation and analysis of the results. The results obtained that are significant to user satisfaction are only the variable perceived ease of use. While the variables content, accuracy, format, ease of use, perceived usefulness and timeliness are not significant to user satisfaction.